A Tool for Appraising Mobility Environment with a Percept Based Index Measure - AbdulMajeed Olaremi Shittu; Muhammad Zaly Shah (TeMA: Journal of Land Use, Mobility and Environment, 2015)
Diverse methods, approaches and models have been employed in explaining mobility in both the urban and human context. However, there has been the ever-present drawback premised on data unavailability, “dyrtiness” or scantiness. More so, the techniques and parameters used, does not provide clues about mobility complexities engendered by attributes of “mobility environments”, as a result, determinants of mobility complexities are hardly fully described. To narrow the gap, it is conjectured that systematic evaluation of traveler perception of “mobility environments”, may provide hints about the degree to which specified spatial units enhance or hinder mobility, by rating such environment with a perception based index construct we hope will help improve assessments of “mobility environments”. This need is underscored by the necessity to explore alternative decision support tools, for mobility evaluations, especially where it may be implausible to apply advanced, high end, data hungry models of mobility evaluation. The method involved a two-pronged survey of transport professionals and randomly selected travelers. The professionals helped with “mobility environment” attributes identification and selection of contextually relevant ones from a list of potential attributes of influence, extracted from relevant literature using the Delphi method. Randomly selected travelers were in turn presented with the short listed attributes for rating on a five point Likert scale. Ratings were then used to determine attribute rankings and their commensurate index equivalents, as a basis for classification. Travelers indicated that a high activity mix, high road and pedestrian network density are good mobility enhancing qualities a city should possess. However, aggregate indexing indicated that enhancing development characteristics, mode characteristics, travel and economic attributes, are the most important for the study area. The measures are targeted at facilitating development of cost effective and parsimonious means of identifying urban mobility challenges by local authorities, to provide a strategic pathway for a city’s “mobility environments” qualities to be identified and objectively appraised, in order to satisfactorily target interventions at improving both the “mobility environment” and the quality of life of city inhabitants.